2023
DOI: 10.1093/jncimonographs/lgad010
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetics of cancer therapeutics and energy balance: the role of diet intake, energy expenditure, and body composition

Abstract: Energy balance accounts for an individual’s energy intake, expenditure, and storage. Each aspect of energy balance has implications for the pharmacokinetics of cancer treatments and may impact an individual’s drug exposure and subsequently its tolerance and efficacy. However, the integrated effects of diet, physical activity, and body composition on drug absorption, metabolism, distribution, and excretion are not yet fully understood. This review examines the existing literature on energy balance, specifically… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 98 publications
0
3
0
Order By: Relevance
“…This discrepancy might be because the Japanese have a lower BMI than Westerners, which might be caused by their food habits. It has been reported that energy balance including body composition and nutritional status could influence on pharmacokinetics of cancer therapeutics 29 , and the habits may influence racial differences in these adverse effects. Nausea and fatigue can affect quality of life particularly if persistent, and it is therefore important to educate and inform the patient of these adverse effects, and proactive efforts should be taken to prevent and treat nausea.…”
Section: Discussionmentioning
confidence: 99%
“…This discrepancy might be because the Japanese have a lower BMI than Westerners, which might be caused by their food habits. It has been reported that energy balance including body composition and nutritional status could influence on pharmacokinetics of cancer therapeutics 29 , and the habits may influence racial differences in these adverse effects. Nausea and fatigue can affect quality of life particularly if persistent, and it is therefore important to educate and inform the patient of these adverse effects, and proactive efforts should be taken to prevent and treat nausea.…”
Section: Discussionmentioning
confidence: 99%
“…The sizes of parts of the body composition are associated with the distribution of the drug. Hydrophilic drugs are dispersed in non-fatty compartments while lipophilic drugs are dispersed in fatty compartments [13]. How the absorption, distribution and elimination of chemotherapeutics associated with ascites volume are affected in our daily practices and whether an appropriate plasma concentration is achieved or not has been a subject of interest.…”
Section: Discussionmentioning
confidence: 99%
“…In particular, body composition is useful for determining energy requirements because lean tissue is more metabolically active than adipose tissue [ 1 ], and quantifying fat mass (FM) aids in determining inadequate or excess energy stores [ 2 ]. In addition, measurement of lean and FM can be informative for determining medication doses [ 3 , 4 ], disease effects [ 5 , 6 ], and other types of biological research [ 7 ].…”
Section: Introductionmentioning
confidence: 99%